Determination of Antibacterial and Antioxidant Properties of Naturally Fermented Orange (Citrus sinensis) Peel Vinegar - Aydın Karaağaç, Ruhşen; Gün, Mervenur (Saglik Bilimleri Fakültesi, Kastamonu University, 2024)
In this study, the antioxidant and antibacterial properties of vinegar produced using traditional methods from orange peel was investigated. Orange peel contains high amounts of biologically active substances such as phenolic compounds, flavonoids, and vitamin C. These compounds have the potential to inhibit the proliferation of microorganisms and neutralize free radicals. The agar diffusion method was used to investigate the antibacterial effect of orange peel vinegar on the test microorganism Escherichia (E.) coli . The results showed that E. coli was sensitive to orange peel vinegar. 2,2-difenil-1-pikrilhidrazil (DPPH) and 2,2’-azinobis (ABTS) Radical Scavenging Assay, Fe3+, and Fe3+-TPTZ Reducing Capacity Assay properties of orange peel vinegar were determined. Orange peel vinegar helps digestion and supports immunity thanks to the vitamin C, natural acids and bioactive compounds it contains. This study also presents an innovative approach for the biotechnological evaluation of waste orange peels and contributes to environmental sustainability. This use of fruit peels offers a sustainable approach to recycling agricultural by-products by addressing environmental concerns related to waste disposal.
Keywords: Orange peel; vinegar; Antibacterial Activity; Antioxidant Activity; Portakal kabuğu; sirke; Antibakteriyel Aktivite; Antioksidan Aktivite; Pharmaceutical Microbiology; Farmasotik Mikrobiyoloji